O’NEILL, P. Trilingual Joyce: The Anna Livia Variations. Toronto: University of Toronto Press, 2018. - Oliveira, Leide Daiane de Almeida (Revista da Anpoll, 2019)
O’NEILL, P. Trilingual Joyce: The Anna Livia Variations. Toronto: University of Toronto Press, 2018.